Progressive Wallerian Degeneration of the Corpus Callosal Splenium in a Patient with Alexia without Agraphia: Advanced MR Findings. Issue 6 (December 2014) - Gandhi, Kriti; Gillihan, Laura; Wozniak, Marcella A.; Zhuo, Jiachen; Raghavan, Prashant
The corpus callosal splenium is an uncommon location for Wallerian degeneration (WD), which may be mistaken for new pathology on magnetic resonance imaging (MRI). We describe the case of a 69-year-old woman with a left posterior cerebral artery infarct in whom progressive WD of the splenium of the corpus callosum seen on MRI was misinterpreted as new infarction or neoplasm. We address how magnetic resonance spectroscopy, perfusion MRI, diffusion tensor MRI, and serial imaging were utilized in establishing the correct diagnosis. Interestingly, the patient also presented with alexia without agraphia, which has never been reported in association with splenial WD. It is conceivable that WD affected critical splenial association fibers resulting in this uncommon dissociation syndrome.